Field efficacy of urease inhibitors for mitigation of ammonia emissions in agricultural field settings: a systematic review - Matse, Dumsane Themba; Krol, Dominika J.; Richards, Karl G.; Danaher, Martin; Cummins, Enda; Wang, Xin; Forrestal, Patrick J. (Frontiers in Environmental Science, 2024)
Globally, ammonia (NH3) is one of the key air pollutants and reducing NH3 emissions and the associated indirect emission of the greenhouse gas nitrous oxide remains challenging for the agricultural sector. During the past three decades, a number of urease inhibitors have been placed on the market with the goal of reducing NH3 loss from urea containing fertilisers. N-(n-butyl) thiophosphoric triamide (NBPT), N-(2-nitrophenyl) phosphoric triamide (2-NPT), and a 3:1 ratio of NBPT + N-(n-propyl) thiophosphoric triamide (NPPT) and the maleic and itaconic acid co-polymer (MIP) are registered urease inhibitors under the European Commission Fertilising Products Regulation (FPR). However, the availability of several inhibitor options has raised questions from farmers, policy makers, and emissions inventory compiling authorities regarding the field efficacy of the different options available for reducing NH3 loss. Despite many disparate NH3 field studies existing for NBPT, 2-NPT, NBPT+NPPT, and MIP there is presently no review that brings these results together, a significant and important knowledge gap. This review addresses the gap by summarising the published field trial literature on NH3 volatilisation mitigation offered by NBPT, 2-NPT, NBPT+NPPT and MIP. Our review identified 48 peer reviewed studies where NH3 loss mitigation was measured in a field setting, giving 256 replicated comparisons. The synthesised literature results revealed that NBPT+NPPT reduced NH3 loss by 75% (95% CI=58-82% n = 32), 2-NPT reduced NH3 loss by 70% (95% CI=63-76% n = 19) and NBPT reduced NH3 loss by 61% (95% CI=57-64% n = 165), giving on average a 69% reduction by these three urease inhibitors. In contrast, MIP increased NH3 loss by 0.3% on average (95% CI= -8 to 9% n = 40). The results presented in this review broaden the understanding of urease inhibitor efficacy in field conditions and demonstrate that not all products behave the same in terms of field NH3 reduction efficacy. This review is important for farmers, policy makers, emission inventory compilers and other stakeholders.